Recent Progress in Curcumin: Extraction, Purification, and Bioactivity - Cao, Hong-Mei; Zhao, Pei-Hong; Zhao, Yi-Tao; Fang, Jiao-Jiao; Wang, Ya-Nan; Chen, Xin (Current Medicinal Chemistry, 2026)
Curcumin is a natural plant pigment that has been widely used in food production, drug development, and textile engineering. Gaining a deep understanding of the biological activities of curcumin and obtaining high-purity curcumin are of vital importance for basic research and applications of curcumin. In this review, we summarize recent advances in curcumin, mainly focusing on the methods of extracting and purifying curcumin from turmeric as well as applications based on biological activity. We systematically describe the advantages and disadvantages of traditional and modern extraction technologies. The usual purification methods include conventional methods (such as macroporous resin column chromatography and silica gel column chromatography, etc.) and auxiliary modern technologies (such as high-speed countercurrent chromatography and supercritical fluid chromatography). In terms of biological activity, the phenolic hydroxy group and methoxy group of curcumin are closely related to its antioxidant activity, endowing it with strong antibacterial, anti-inflammatory, and antitumor properties. Moreover, the development direction based on its multiple biological activities is also discussed.
Keywords: extraction